Peningkatan Keamanan dan Kualitas Penyembelihan Hewan Kurban melalui Inovasi Alat Perebah - Qodratulloh S, Waway; Nuryuliyawati, Sri; Qolbi, Satria Kharimul; Arif Nugraha, Muhamad; Yunus Maulana, Muhammad; Amanda Ainun Nuzul, Dinda; Gufron, Hilman (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The slaughtering of sacrificial animals (kurban) is a religious ritual rich in spiritual, social, and health values; however, in practice, it still faces several fundamental challenges. The traditional method of casting animals with ropes often poses safety risks to the committee, causes stress to the animals, and leads to a decline in meat quality. This community service program was conducted to provide a solution through the innovation of a safe and efficient animal casting tool that complies with Islamic principles. The method consisted of needs assessment, design and fabrication of a galvanized steel frame casting device with a portable hinge system, training on hygienic and syar’i slaughtering techniques, and field trials with the kurban committee. The results showed that the casting tool significantly reduced accident risks, shortened the time required for animal handling and slaughter, and maintained meat quality by minimizing animal stress. Moreover, the training improved the skills and knowledge of the kurban committee, particularly in halal, hygienic, and regulated slaughtering practices. The success of this program provided not only a technical solution but also reinforced the religious and social values of the kurban ritual, while fostering community independence in applying appropriate technology. Therefore, this community service contributes to enhancing safety, meat quality, and the sustainability of an orderly, hygienic, and syar’i-compliant kurban tradition.